Imperceptible and secure image watermarking using DCT and random spread technique - Eko Hari Rachmawanto; De Rosal Ignatius Moses Setiadi; Christy Atika Sari; Nova Rijati (Universitas Ahmad Dahlan, 2019)
Watermarking is a copyright protection technique, while cryptography is a message encoding technique. Imperceptibility, robustness, and safety are aspects that are often investigated in watermarking. Cryptography can be implemented to increase watermark security. Beaufort cipher is the algorithm proposed in this research to encrypt watermark. The new idea proposed in this research is the utilization of Beaufort key for watermark encryption process as well as for spread watermark when inserted as PN Sequence substitute with the aim to improve imperceptibility and security aspects. Where PN Sequence is widely used in spread spectrum watermarking technique. Based on the experimental results and testing of the proposed method proved that imperceptibility and watermark security are increased. Improved imperceptibility measured by PSNR rose by about 5dB and so did the MSE score better. Robustness aspect is also maintained which has been proven by the excellent value of NCC.